Mining Association Rules for Web Crawling using Genetic Algorithm - Dr. K. Iyakutti,, J. Usharani (International Journal of Engineering and Computer Science, 2017)
With the recent advancement of Internet and Web Technology, web search has taken an important role in our ordinary life. A Web crawler is a software program that automatically retrieves the Web pages when a query is placed in the search engine. To discover interesting patterns or relationship between data in large database Association rule mining is used. Association rule mining can be an important data analysis method to discover associated web pages. The Apriori algorithm is a proficient algorithm for determining all frequent web pages. The Frequent web pages form the Association rules. We proposed a novel approach - genetic based apriori algorithm for web crawling. The proposed method yields promising results compared to the ordinary apriori algorithm and we present empirical results to substantiate this claim.